The twilight queen - Westerson, Jeri (Westerson, Jeri. King's fool mystery., 2024)
"1536, London. Anne Boleyn, Queen of England, is in peril. In the mid of night, court jester Will Somers is summoned to an urgent assignation when she discovers a body in her chamber. The queen wants Will to find out who the man is and how he ended up there. Is someone trying to frame her for his murder? Queen Anne has many enemies at court, and to make matters worse, Henry VIII is lining up his next conquest and suspects his queen of treason. Has the formidable Thomas Cromwell been whispering vile lies in the king's ears, and could the queen be the target of a Catholic conspiracy? As further attacks plague the court, Will is determined to uncover the truth behind the plotting and devilry, but he will need to keep hold of all his wits to do so!"--